2011
DOI: 10.1097/md.0b013e318206af16
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Follow-Up of Upper and Lower Extremity Vasculitis Related to Giant Cell Arteritis

Abstract: We conducted this retrospective study to determine the prevalence of giant cell arteritis (GCA) in patients exhibiting nonatherosclerotic upper and/or lower extremity arterial involvement and to evaluate the clinical features and long-term outcome of those patients.From January 1997 to March 2008, 36 consecutive patients in the Department of Internal Medicine at the University of Rouen medical center received a diagnosis of symptomatic upper/lower extremity vasculitis related to GCA. In the 36 patients, upper/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
47
0
10

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(62 citation statements)
references
References 82 publications
5
47
0
10
Order By: Relevance
“…In contrast to atherosclerotic etiology, ischemic symptoms in patients with GCA progressed rapidly and lead to development of limb-threatening ischemia within very short of time (15). Assie and his colleagues came up with similar results demonstrating a common presence of upper and lower extremity involvement in GCA even in early phase of disease (16). According to published cases prognosis of limb involvement is quite variable, patients with critical limb ischemia frequently undergo revascularisation treatment.…”
Section: Giant-cell Arteritissupporting
confidence: 60%
“…In contrast to atherosclerotic etiology, ischemic symptoms in patients with GCA progressed rapidly and lead to development of limb-threatening ischemia within very short of time (15). Assie and his colleagues came up with similar results demonstrating a common presence of upper and lower extremity involvement in GCA even in early phase of disease (16). According to published cases prognosis of limb involvement is quite variable, patients with critical limb ischemia frequently undergo revascularisation treatment.…”
Section: Giant-cell Arteritissupporting
confidence: 60%
“…6 Assie et al also observed a lower rate of positive temporal artery biopsy in patients with temporal artery GCA compared to those with involvement of upper and lower limb arteries (69% vs. 95%). 7 Biopsy of the affected artery is generally only available if revascularization procedures take place, so the diagnosis and treatment strategy of large-vessel GCA are frequently decided before histological results are available. The biopsy may reveal transmural inflammatory infiltrate with fragmentation of the elastic lamina with or without giant cells in a focal and segmental distribution.…”
Section: Discussionmentioning
confidence: 99%
“…Reconstructive study was performed in 10 patients. Histology of the vessels was obtained only in the 2 patients who underwent limb amputation; histologic analyses of vessel tissues showed damage consistent with active GCA [8] . Recently, some reports have suggested that TA and GCA are the same disease, because the histopathologic features are indistinguishable [9] .…”
Section: Discussionmentioning
confidence: 99%
“…Assie et al reported that all patients with extremity vasculitis related to GCA were given steroid therapy at a median daily dose of 1 mg/kg predonisolone initially and immunosuppressive drugs (MTX, azathioprine, or cyclophosphamide) were added in some patients [8] . In the present case, we initiated high-dose oral prednisolone (1 mg/kg/day) and then added MTX.…”
mentioning
confidence: 99%